Self-Perceived Facial Attractiveness, Fluctuating Asymmetry, and Minor Ailments Predict Mental Health Outcomes - Borráz‑León Javier I; Rantala Markus J.; Luoto Severi; Krams Indrikis A.; Contreras‑Garduño Jorge; Krama Tatjana; Lilia Cerda-Molina Ana (SPRINGER HEIDELBERG, 2022)
Objective Phenotypic markers associated with developmental stability such as fluctuating asymmetry, facial attractiveness, and reports of minor ailments can also act as indicators of overall physical health. However, few studies have assessed whether these markers might also be cues of mental health. We tested whether self- and other-perceived facial attractiveness, fluctuating asymmetry, and minor ailments are associated with psychopathological symptoms in a mixed sample of 358 college students, controlling for the effects of body mass index, age, and sex.
Methods We applied the Symptom Checklist-90-Revised (SCL-90-R) questionnaire to assess psychopathological symptoms, a battery of questionnaires about self-perceptions of facial attractiveness, and gathered information about the number of previous minor ailments as well as demographic data. Other-perceived attractiveness was assessed by an independent mixed sample of 109 subjects. Subjects' facial fluctuating asymmetry was determined by geometric morphometrics.
Results The results revealed that in both men and women, higher self-perceived attractiveness and fewer minor ailments predicted lower scores of Somatization, Obsessive-Compulsive, Interpersonal Sensitivity, Depression, Anxiety, Phobic Anxiety, Paranoid Ideation, Psychoticism, and a General Psychopathology Index. Higher facial fluctuating asymmetry was associated with higher Interpersonal Sensitivity, but did not contribute to its prediction when controlling for the other studied variables.
Conclusions The observed strong associations between self-perceived attractiveness, minor ailments, and psychopathology indicate common developmental pathways between physiological and psychological symptomatology which may reflect broader life history (co)variation between genetics, developmental environment, and psychophysiological functioning.